Complete mitochondrial genome of the wild Diptychus maculatus (Cypriniformes, Cyprinidae, Schizothoracinae) from Yeken River using next generation sequencing and the phylogenetic relationship of Cyprinidae species. Issue 1 (2nd January 2020) - Niu, Jiangong; Zhang, Yu; Liu, Hong; Hu, Jiangwei; Cai, Lingang; Zhang, Renming; Zhang, Hui
Abstract: The complete mitochondrial genome of the wild Diptychus maculatus collected from Yeken River was determined using next generation sequencing. The mitogenome is a circular molecule 16, 765 bp in length, including 13 protein-coding genes, two ribosomal RNA genes, 22 transfer RNA genes, and a control region. The TAS, central CSB, and CSB were detected in the control region. The gene contents of the mitogenome are identical to those observed in most bony fishes. The NJ phylogenetic tree showed that D. maculatus clustered into one separate branch which is close to genus Gymnodiptychus from the same subfamily.